Reorienting the cultural script of teaching: cross cultural analysis of a science lesson. Issue 3 (30th September 2014) - Reza Sarkar Arani, Mohammad; Shibata, Yoshiaki; Christine Lee, Kim-Eng; Kuno, Hiroyuki; Matoba, Masami; Lay Lean, Fong; Yeo, John
Abstract : Purpose: – The purpose of this paper is to reveal the cultural script of the teaching of a lower secondary science lesson on the topic "Classification of Non-living Things" in Singapore through the eyes of Japanese and Singaporean researchers and teachers. In particular, the study analyzes the structural content, i.e. organization of learning activities of a lower secondary science lesson of Singapore and the culture of teaching, i.e. views about teaching held as tacit knowledge of science teachers. It focusses on students' inquiry skills in a participative and problem-driven science lesson in the Singapore classroom. Design/methodology/approach: – This exploratory study adopts a cultural approach of viewing teaching and learning and compares classroom practice in two countries – Japan and Singapore. Contextually, the cultural differences in beliefs and values define how educators learn about what is "good" teaching. Findings: – The cultural script of teaching of the science lesson case values the setting of learning tasks that encourage a variety of ideas. It also sets a tone of inquiry-based learning where students are open to questioning, the formulation of ideas and the presentation of solutions. In the science lesson case, the teacher aimed at providing opportunities for students to think for themselves and to engage in group discussion. This study identifies key aspects of the science lesson for revealing the teaching script based on a cross-cultural lesson analysis. Figure 1 summarizes such facets of teacher teaching and student learning in detail as a result of the lesson analysis. Furthermore, it draws attention to recognizing areas of the lesson script which the Japanese team found effective/ineffective as well as identifying the Singaporean team's reflections on feedback from Japanese educators. Research limitations/implications: – Through this study, the research team raises the following questions. Are there common practices that make for effective learning and if so what are these? From the perspectives of Japanese and Singaporean researchers and educators, what might be the different elements of teaching that will bring about better student learning? Originality/value: – An important avenue for inquiry in teaching is how to create teaching-learning processes that nurture students' ability to deal with the unexpected as well as their application skills – competencies that are required of students to function in the twenty-first century. The research team suggests a cross-cultural analysis approach for future research investigating the cultural script of teaching.